THE PRAXIS OF INTEGRATING VIRTUAL REALITY INTO VOCABULARY TEACHING TO YOUNG LEARNERS - Nia Kurniawati; Anisa Sofarini; Elis Homsini Maolida; Rahmat Taufiq Dwi Jatmika (University of Kuningan, 2022)
In this digital age, using technology to teach English has become commonplace. This study focuses on the integration of virtual reality (VR) into vocabulary teaching to young learners. The aims of the study are finding out the teacher's classroom practices, the challenges, and the young learners’ views of VR integration in learning vocabulary. In this study, a case study was applied in conjunction with observation, an open-ended questionnaire, and an interview to uncover the concerns. The respondents were an English teacher and 40 students of fifth grade at SDN 1 Cipanas, Cianjur. Despite the fact that the teacher was able to incorporate VR into her English classroom, there are also some challenges discovered during the practice. School readiness in terms of device availability, teacher’s TPACK level, workloads, teaching media, and classroom managerial skills became the primary issues in the language instruction using VR. Furthermore, the proficiency, characteristics, and quantity of students in the classroom must also all be taken into account. To young learners, on the other hand, learning vocabulary using VR is engaging and entertaining, even if prolonged exposure to the VR lens causes headaches. It is recommended that policymakers pay greater attention to providing more supportive policies and improved facilities for TEYL practice in Indonesia.